Mineral chemistry, bulk rock geochemistry, and S‐isotope signature of lode‐gold mineralization in the Bétaré Oya gold district, south‐east Cameroon. (13th December 2017) - Vishiti, Akumbom; Suh, Cheo Emmanuel; Lehmann, Bernd; Shemang, Elisha Mutum; Ngome, Njumbe Lionel Junior; Nshanji, Nfor Jones; Chinjo, Fonkwo Edmond; Mongwe, Oben Yoland; Egbe, Ashu Jones; Petersen, Sven
Abstract : Lode‐gold mineralization in the Bétaré Oya gold district is related to a series of quartz–sulphide veins that define a steeply dipping NNE–SSW‐trending brittle–ductile shear zone. The veins transect metasedimentary sequences in the vicinity of small granitic intrusions. Quartz veins range from barren (massive quartz) to mineralized with textures that vary from foliated, sheared, vuggy, fractured, and sugary to brecciated with inclusions of altered wall rock. They contain gold, pyrite, and galena in addition to chalcopyrite and both hypogene and supergene haematite and covellite. Parameters that consistently define primary gold mineralization in the area include silicification, sulphidation, sericitization, K‐feldspar alteration, haematitization, and carbonatization. Gold grains recovered from heavy mineral concentrate and grains that occur as inclusions in pyrite were characterized by microchemical methods. The gold grains are zoned and exhibit a simple internal structure of partly deformed and leached rims and high‐purity intragranular veinlets. Gold is alloyed with Ag; gold fineness varies between 859 and 877 in the core and from 958 to 997 in the leached rims. Inclusions of gold in pyrite cluster between 875 and 900. Pyrite has up to 0.59 wt% Au, and other trace elements occur in low quantities but for Pb (0.13 wt%), Ag (1.36 wt%), and Sb (1.63 wt%). The bulk trace element signature of the veins is characterized by Au, Ag, As, Bi, Ba, Cr, Cu, Mn, Pb, Sb, Sr, V, W, Zn, and Zr. This depicts a geochemical association of Au ± Cu ± Bi ± As ± Pb. The occurrence of Au as well as elevated Pb and Zn could suggest a granitic source for the ore‐bearing fluid. The auriferous quartz veins are characterized by a widespread in δ 34 S from 2.8 to 14.9‰ pointing to multiple sources of sulphur in the system, perhaps a mixture of sulphur from the metasedimentary and the granitic rocks.